2020
DOI: 10.3390/ijms21124246
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Potential Bovine Spongiform Encephalopathy (BSE)-Related Somatic Mutation E211K of the Prion Protein Gene (PRNP) in Cattle

Abstract: Bovine spongiform encephalopathy (BSE) is a prion disease characterized by spongiform degeneration and astrocytosis in the brain. Unlike classical BSE, which is caused by prion-disease-contaminated meat and bone meal, the cause of atypical BSE has not been determined. Since previous studies have reported that the somatic mutation in the human prion protein gene (PRNP) has been linked to human prion disease, the somatic mutation of the PRNP gene was presumed to be one cause of prion disease. However, to the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…To date, although extensive investigations on 211K germline mutation have been performed in the United States and Korea, the cattle carrying 211K germline mutation have not been reported thus far (Heaton et al., 2008; Kim & Jeong, 2017). However, recently, we identified potential BSE‐related somatic mutation E211K in 3 Korean Holstein cattle (Won et al, 2020). Furthermore, previous studies have reported that the 23‐bp insertion/deletion polymorphism in the promoter and the 12‐bp insertion/deletion polymorphism in intron 1 of the bovine PRNP gene have been strongly associated with the expression level of bovine prion protein and modulate susceptibility to BSE in cattle (Haase et al., 2007; Jeong et al., 2006; Sanches et al., 2016; Vernerova et al., 2014; Zhao et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To date, although extensive investigations on 211K germline mutation have been performed in the United States and Korea, the cattle carrying 211K germline mutation have not been reported thus far (Heaton et al., 2008; Kim & Jeong, 2017). However, recently, we identified potential BSE‐related somatic mutation E211K in 3 Korean Holstein cattle (Won et al, 2020). Furthermore, previous studies have reported that the 23‐bp insertion/deletion polymorphism in the promoter and the 12‐bp insertion/deletion polymorphism in intron 1 of the bovine PRNP gene have been strongly associated with the expression level of bovine prion protein and modulate susceptibility to BSE in cattle (Haase et al., 2007; Jeong et al., 2006; Sanches et al., 2016; Vernerova et al., 2014; Zhao et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the exact cause of conversion of PrP C to PrP Sc has not been reported. However, recently, it has been presumed that PRNP genetic mutations, posttranslational modifications, and several genetic factors play a pivotal role in the conversion process of PrP C to PrP Sc [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, differences in the local crystal structure of the TLR4-MD2-LPS complex were noted between TLR4 with the wild type allele and the G299 allele [ 20 , 21 ]. Since genetic variations confer functional alteration, these studies indicate that the rs4986790 SNP of the TLR4 gene is related to anti-bacterial functions of TLR4 [ 22 , 23 , 24 ]. Interestingly, TLR4/MD2 complex directly interacts with the Tat protein of HIV-1, and HIV-1 modulates the expression level of TLR4 and downstream immune responses, including the NF-κB pathway [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%